2014
DOI: 10.1093/europace/euu306
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponin levels following implantable cardioverter defibrillation implantation and testing

Abstract: Implantation of ICD leads was associated with release of troponin, but we did not observe any evidence that ICD shocks alone cause myocardial injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
2
14
1
Order By: Relevance
“…"Catecholamine overload" (ref. [27][28][29] or direct mechanical damage [30][31][32][33][34][35][36][37][38][39] during skiascopy of the heart (during pacemaker implantation) can be a marker of procedure complexity and may positively correlate with troponin levels 31 . Left ventricular failure 40 , right ventricular failure [41][42][43] , or the disparity between physiological degradation of the myocardium and insufficient elimination of its fragments (renal insufficiency) (ref.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…"Catecholamine overload" (ref. [27][28][29] or direct mechanical damage [30][31][32][33][34][35][36][37][38][39] during skiascopy of the heart (during pacemaker implantation) can be a marker of procedure complexity and may positively correlate with troponin levels 31 . Left ventricular failure 40 , right ventricular failure [41][42][43] , or the disparity between physiological degradation of the myocardium and insufficient elimination of its fragments (renal insufficiency) (ref.…”
Section: Methodsmentioning
confidence: 99%
“…In a 2015 study published by Furniss 38 , increased levels of troponin T in patients undergoing simple ICD implantations both with and without discharge therapy were observed. There were no differences in troponin T elevation between the two groups and no differences in the dependence on total energy applied during test discharge.…”
mentioning
confidence: 99%
“…There was a significant correlation between the number of leads implanted and the percent change in hs-cTnT (r = 0.51, p = 0.01), but no correlation between the number of shocks (r = 0.26, p = 0.25) or the total delivered energy (r = 0.24, p = 0.30) and percent change in hs-cTnT levels. 36 This suggests that, although device implantation and lead deployment may cause an increase in hs-cTn levels, ICD shocks alone do not appear to cause hs-cTn elevation. In addition, the prognostic implication of elevated hs-cTn in ICD patients has yet to be investigated and warrants future examination.…”
Section: Sudden Cardiac Death and Cardiac Arrestmentioning
confidence: 99%
“…In a prospective study, Furniss et al 36 examined hs-cTn levels and electrocardiogram changes during ICD implantation without defibrillation threshold testing (DFT), ICD implantation with DFT, and DFT as a standalone procedure. There was no significant change in hs-TnT levels in a group of patients undergoing defibrillation testing alone compared with baseline levels, while hs-TnT was significantly higher in patients undergoing implantation alone (median increase 96%, p = 0.005) and in patients undergoing implantation and testing (median increase 161%, p = 0.005).…”
Section: Sudden Cardiac Death and Cardiac Arrestmentioning
confidence: 99%
“…Implantation of ICD leads has been associated with release of troponin, but there is no clear evidence that ICD shocks alone cause myocardial injury. In fact, Guy et al [70] studied 32 patients who underwent a total of 34 procedures and found that implantable cardioverter defibrillator implantation and testing is associated with release of cardiac troponin and is correlated to the number of ventricular lead deployments during the procedure. Secondly, they also noted that implantable cardioverter defibrillator testing conducted as a stand-alone procedure does not result in the release of cardiac troponin [70].…”
Section: Defibrillator Shocksmentioning
confidence: 99%